Implementasi Teknologi Pembuatan Ecoenzyme dari Limbah Rumah Tangga di Kampung Morten, Melaya, Malaysia - Ika Dyah Kumalasari; Utaminingsih Linarti; Retnosyari Septiyani (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Fruit peel waste has the potential to be utilized as an eco-enzyme. Eco-enzyme can be used in sanitation and hygiene. Kampung Morten is a tourist village in the city of Melaka, Malaysia. As a tourist village, the problem of utilizing organic waste is a problem that needs to be addressed by the Kampung Morten Community. The purpose of this study is to provide training to improve knowledge and skills in processing fruit peel waste through the implementation of integrated technology with science. The method of implementing this program is through socialization, training in making eco-enzymes using the fermentation method, measuring achievements using questionnaires and interviews, and mentoring. Based on the results of the implementation, it shows that the activities/programs carried out were successful because they increased knowledge of organic waste processing and eco-enzymes by 58% and increased skills in processing eco-enzymes from household fruit and vegetable waste by 76%. It is hoped that the efforts and results of this community service can be sustainable for implementation in the Kampung Mrtem Community to improve the economy and socio-culture of processing organic waste from household waste.